Ammopiptanthus nanus Population Dynamics: Bridging the Gap Between Genetic Variation and Ecological Distribution Patterns - Jingdian Liu; Mengmeng Wei; Jiayi Lu; Shiqing Liu; Xuerong Li; Xiyong Wang; Jiancheng Wang; Daoyuan Zhang; Ting Lu; Wei Shi (Biology)
Ammopiptanthus nanus, a Tertiary-era endangered plant, is of great scientific value. In this research, we focus on A. nanus population dynamics in an effort to bridge the divide between micro genetic variation and a macroscopic ecological pattern of distribution. The population structure of 129 wild specimens of A. nanus from eight populations was analyzed using EST-SSR molecular markers in this research. The Mantel test and RDA analysis have been used in this research to investigate the factors that influence the genetic diversity of A. nanus. Using 15 pairs of SSR primers, a total of 227 alleles were detected in 129 samples from 8 populations. The mean number of alleles was 17, and the average expected heterozygosity was 0.405. It is shown that wild A. nanus is divided into six individual populations. A. nanus are significantly affected by wind speed in terms of the variation of genetics. It is suggested that a nature conservation area for A. nanus be established as soon as possible, based on our results and the current natural distribution of the species. It is necessary to focus on the issue of pests and diseases while simultaneously preventing the continuation of anthropogenic woodcutting and disaster. Manual seedling collection should be employed in regions where the environment permits. Through making use of manual breeding techniques, this will contribute to the growth of the natural population of A. nanus.